The social value of a PASI 90 or PASI 100 response in patients with moderate-to-severe plaque psoriasis in Spain - Maravilla-Herrera, Paulina; Merino, María; Alfonso Zamora, Santiago; Balea Filgueiras, Jesús; Carrascosa Carrillo, José Manuel; Delgado Sánchez, Olga; Dolz Sinisterra, Francisco; García-Ruiz, Antonio; Herranz Pinto, Pedro; Manfredi, Antonio; Martínez Olmos, José; Morales de los Ríos Luna, Paloma; et al. (Frontiers in Public Health, 2023)
Psoriasis is a chronic disease involving the skin, which significantly impacts quality of life[1]. Disease severity and treatment efficacy (i.e., response) are assessed through the Psoriasis Area and Severity Index (PASI). A PASI 75 response, i.e., an improvement of at least 75% with respect to baseline PASI, has traditionally been used as a therapeutic benchmark in clinical trials. Therapeutic advances have made PASI 90 or PASI 100 responses possible in most patients treated with some biologics. A greater response may generate social value beyond clinical outcomes through quality of life or labour productivity gains, benefiting both patients and society. We aimed to analyse the social value of achieving PASI 90 or PASI 100 responses in patients with moderate-to-severe plaque psoriasis in Spain. A 1-year economic model was applied to estimate the impact of achieving PASI 75, PASI 90, or PASI 100 responses in four areas of analysis (costs related to reduced quality of life, impairments in activities of daily living, work productivity losses, and out-of-pocket expenditures) and the social value of achieving PASI 90 or PASI 100 responses in comparison with a PASI 75 response. A mixed-methods approach (scientific literature, a patient focus group, and an advisory committee with psoriasis stakeholders) was used. The model included three different scenarios: increasing the response from PASI 75 to PASI 90; from PASI 90 to PASI 100; and from PASI 75 to PASI 100. A sensitivity analysis was included. The social value of achieving a PASI 90 instead of a PASI 75 response would generate an additional social value of € 2,183, and € 4,786 with a PASI 100 response. The annual economic impact per patient with moderate-to-severe psoriasis achieving a PASI 75 response was estimated at € 6,139, mainly related to labour productivity and quality of life. Achieving PASI 90 or PASI 100 responses would reduce this impact to € 3,956 or € 1,353, respectively. Achieving PASI 90 or PASI 100 responses would have a lower economic impact and generate a higher social value than achieving a PASI 75 response for patients with moderate-to-severe plaque psoriasis.